Anmeldelser - Jacobsen, Niels Kingo; Jensen, Ruth Helkiær (Geografisk Tidsskrift, 1965)
INDHOLD Litteraturanmeldelser: FYSISK GEOGRAFI M. M. D. R. Bates: The Planet Earth (N. Nielsen) ............................... 244 A. Austin Miller: The Skin of the Earth (Kr. M. Jensen) ................. 270 H. E. Landsberg & J. van Mieghem: Advances in Geophysics (S. Christiansen) ..................................................... 252 F. J. Pettijohn & P. E. Potter: Atlas and Glossary of Primary Sedimentary Structures (K. Hansen) ................................................ 251 K. Yoshida: Studies on Oceanography (S. Christiansen) ................... 252 M. Sears: Progress in Oceanography (S. Christiansen) ................... 252 H. Stommel: The Gulf Stream (S. Christiansen) .......................... 251 R. L. Wiegel: Oceanographical Engineering (S. Christiansen) ............ 252 S. V. Viktorov, Ye. A. Vostokova, D. D. Vyshivkin: Short Guide to Geo- Botanical Surveying (Kr. M. Jensen) ................................. 269 R. Brewer: Fabric and Mineral Analysis of Soils (K. Hansen) ............ 262 Limnologie der Donau (K. Hansen) ........................................ 250 A. Wechmann: Hydrologie (S. Rasmussen) ............................... 256 W. D. Kingery: Ice and Snow (B. Fristrup) .............................. 255 KULTUR- OG ERHVERVSGEOGRAFI J. W. Morris & O. W. Freemann: World Geography (R. Helkiær Jensen) . . 260 A. E. Haarer: Modern Banana Production (P. Kongstad) ................. 258 Unesco: Land Use in Semi-Arid Mediterranean Climates (P. Kongstad) . . 264 C. B. Troedsson: Architecture, Urbanism and Socio-Political Developments 267 in our Western Civilization (P. Kongstad) ........................ 267 F. S. Chaping & S. F. Weiss: Urban Growth Dynamics (P. Kongstad) ...... 267 K. Meyer: Ordnung im ländlichen Raum (R. Helkiær Jensen) ............ 249 EUROPA OG SOVJETUNIONEN W. Carr: Schleswig-Holstein, 1815-48 (N. Nielsen) ........................ 254 K. F. Gansäuer: Lagerung und Verflechtung der eisenschaffenden Industrie der Montanunionsländer in räumlicher Sicht (V. Hansen) ............ 247 G. Voppel: Die Aachener Rergbau- und Industrielandschaft (V. Hansen) . . 247 Pb. Pinchemel: Geographie de la France (V. Hansen) ..................... 266 British Landscapes Through Maps (V. Hansen) .......................... 246 E. Johns: British Townscapes (V. Hansen) .............................. 245 Land Use in Northern Ireland (V. Hansen) ................................ 246 G. Macesich: Yugoslavia (P. Kongstad) ................................... 258 P. L. Horecky: Russia and the Soviet Union (P. Kongstad) ............... 257 S. I. Floss: Conflict and Decision-Making in Soviet Russia (P. Kongstad) . . 257 FREMMEDE VERDENSDELE F. J. Monkhouse & A. V. Hardy: North American Landscape (V. Hansen) 253 P. J. M. McEwans & R. R. Sutcliffe: The Study of Africa (H. Jeppesen) . . 259 I. G. Stewart & H. W. Ord: African Primary Products and International Trade (H. Jeppesen) .................................................. 259 Samir Amin: Trois experiences africaines de dcweloppement: Le Mali, La Guinee et Le Ghana (H. Jeppesen) ................................... 259 A. J. Toynbee: Retween Niger and Nile (R. H. Jensen) ................... 260 P. Johnsen: Nord for Zambezi (R. H. Jensen) ............................ 269 O. A. Jäger: Antiquities of North Ethiopia (M. Rentsch) ................... 269 L. Frobenius & H. Obermaier: Die afrikanischen Felsbilder. Hadschra Maktuba (M. Rentsch) ..................................... 269 C. Onslow: Asian Economic Development (L. de Castro Lopo) .......... 250 R. Fedden: Syria and Lebanon (P. Kongstad) ............................ 264 E. Orni & E. Efrat: Geography of Israel (S. Illeris) ........................ 265 Charan Singh: India’s Poverty and its Solution (S. Folke) ............... 265 S. G. Davis: Economic Geology of Hong Kong (P. Kongstad) ............ 258 S. G. Davis: Land Use Problems in Hong Kong (P. Kongstad) ............ 259 G. T. Trewartha: Japan, A Geography (S. Christiansen) ................. 253 POLAREGNENE J. Büdel und A. Wirthmann: Vorträge des Fridtjof-Nansen-Gedächtnis- Symposions über Spitzbergen (N. Nielsen) ............................ 256 A. Wirthmann: Die Landformen der Edge-Insel in Südostspitzbergen (B. Fristrup) . ........................................................ 260 G. Wagner: Klimatologische Beobachtungen in Südostspitzbergen 1960 (B. Fristrup) ......................................................... 261 American Geographical Society: Antarctic Map Folio Series (B. Fristrup) . . 255 P. D. Astapenko: Atmospheric Processes in the High Latitudes of the Southern Hemisphere (B. Fristrup) ................................... 261 N. P. Rusin: Meteorological and Radiational Regime of Antarctica (B. Fristrup) .......................................................... 261 ATLASVÆRKER OG KORT P. Thran & S. Broekhuizen: Agro-climatic Atlas of Europe (Kr. M. Jensen) 268 Klima-Atlas von Niedersachsen (Kr. M. Jensen) .......................... 267 Ceskoslovensky Vojensky Atlas (Aa. Aagesen)................................ 248 Atlas der Schweiz (N. Nielsen) ............................................ 254 Norge, bil- og turistkort (N. Nielsen) ...................................... 245 The Prentice-Hall World Atlas (R. H. Jensen) ............................ 249 Atlas Nacional do Brasil (Aa. Aagesen) ................................... 262 NYE TIDSSKRIFTER M. M. Mediterranea (P. Kongstad) .............................................. 258 Russisches Geographisches Namenbuch (N. Nielsen) ..................... 244 B0GER INDGÅET TIL REDAKTIONEN ................ 270 Geografforeningen 271